Arc‐Melting to Narrow the Bandgap of Oxide Semiconductors. (10th March 2015) - Ou, Gang; Li, Dongke; Pan, Wei; Zhang, Qinghua; Xu, Ben; Gu, Lin; Nan, Cewen; Wu, Hui
<x xml:space="preserve">Abstract</x> The bandgap of a series of oxide semiconductors is narrowed by a quick and facile arc‐melting method. A defective structure is formed in the fast melting and cooling process without changing its phase structure. Enhanced optical and electrical properties are found in the arc‐melted oxide, such as enhanced photocatalytic properties of the arc‐melted ZnO under visible light. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>